De novo synthesis of bacterial glycogen: Agrobacterium tumefaciens glycogen synthase is involved in glucan initiation and elongation - Ugalde, Juan E. (National Academy of Sciences, 2003)
Evidence is presented indicating that initiation of glycogen synthesis in Agrobacterium tumefaciens does not require the presence of α(1,4)-linked glucans. Crude cell extracts incubated with ADP-glucose (Glc) were able to form α(1,4)-linked glucans despite the fact that cells used for extract preparation displayed a genotype that prevented synthesis of Glc-containing sugar nucleotides and thus preformation of α(1,4)-linked glucans and that the defined growth medium used contained glycerol as carbon source. A. tumefaciens glycogen synthase (GS) purified to homogeneity from the above-mentioned cells was able to build its own primer by transferring Glc residues from ADP-Glc to an amino acid(s) in the same protein. Primed GS then became the substrate for further GS-catalyzed glucan elongation. It was concluded that, contrary to what happens in mammalian and yeast cells in which two different proteins are required for linear α(1,4)-linked glucan formation (glycogenin for initiation and GS for further elongation), in A. tumefaciens and probably in all other bacteria, the same protein is involved in both glycogen initiation and elongation.